Hubungan Antara karakteristik Ibu Rumah Tangga Dengan Pengetahuan Kesehatan di Kabupaten Malang dan Pamekasan Jawa Timur 1984 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK Before the implementation of the "Communication Pilot Project To Support Basic Social Services", a preliminary study was conducted in the Malang and Pamekasan Districts. The results of the study were as follows : 39% and 50% respectively, of the respondents in Malang and Pamekasan do not have formal education.